The Effect Of Service Quality And Promotion On Consumer Purchase Decisions At PT. Sumber Alfaria Trijaya, Tbk (Alfamart) Bintaro Utama Branch, South Tangerang City - Khulsum, Yulia; Jasmani, Jasmani (Kompartemen: Kumpulan Orientasi Pasar Konsumen, 2024)
This study aims to determine the effect of service quality and promotion on consumer purchasing decisions at PT Sumber Alfaria Trijaya, Tbk (Alfamart) Bintaro Utama Branch, South Tangerang City. The method used is explanatory research with analysis techniques using statistical analysis with regression testing, correlation, determination and hypothesis testing. The results of this study show that service quality has a significant effect on consumer purchasing decisions by 52.0%, the hypothesis test obtained t count> t table or (10.302> 1.984). Promotion has a significant effect on consumer purchasing decisions by 45.9%, the hypothesis test obtained t count> t table or (9.112> 1.984). Service quality and promotion simultaneously have a significant effect on consumer purchasing decisions with the regression equation Y = 5.903 + 0.480X1 + 0.378X2 and a contribution of 63.4%, the hypothesis test obtained F count> F table or (83.904> 2.700).